Peran Chatbot Artificial Intelligence (AI) sebagai Teman Virtual: Literature Review - Andri Sahata Sitanggang; Irsan Ahmad Syawali; Sulthan Firman Hafizh; Fauzan Zaki Sholih; Muhammad Alwizard; Albertus Aris Nauw (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
The development of digital technology has brought about significant changes in the way humans communicate and live their daily lives. One important innovation is Artificial Intelligence (AI), one tangible manifestation of which is the chatbot as a virtual friend. This study aims to examine the role of chatbots as virtual friends through a literature review approach. The results of the study indicate that chatbots can serve as a potential, easily accessible tool for providing emotional support. Chatbots are able to create a safe space for users, especially Generation Z, to express themselves and overcome loneliness. However, the relationship between humans and chatbots is complex. Chatbots can mimic supportive responses, but as algorithmic systems, their ability to experience true empathy is very limited. Users' awareness that responses are coming from a machine also influences perceptions of trustworthiness and the quality of the interaction. On the other hand, the use of chatbots also raises serious ethical challenges, such as data privacy issues, the potential for over-dependence, and increased loneliness if chatbots are used as a substitute for real social interaction. Therefore, the development and use of chatbots as virtual friends must be carried out with a critical understanding and ethical approach. Technology design oriented towards humanitarian values is needed so that the presence of chatbots does not diminish the essence of human relationships but instead becomes a psychosocially beneficial complement.